Sistem Informasi Geografis Persebaran Madrasah Aliyah (MA) Menurut Kecamatan di Kabupaten Jepara - Agesti, Okta Vian; Bambang Agus Herlambang (CV. ALIM'SPUBLISHING, 2023)
Jepara Regency, Central Java, provides several private Aliyah Madrasahs as an option to study. High School is an important stage that must be undertaken by students. There are still many people who find it difficult to find information about schools and their locations because of the lack of these sources of information. Students will feel more comfortable while studying at the school of their choice, which can also increase learning motivation. Many students experience confusion when they want to apply to their favorite schools in Jepara due to lack of information about school choices. Jepara Regency has a variety of Madrasah Aliyah, including private and public ones. This application is designed in web format and based on Geographic Information System, with the hope that it can provide convenience for prospective students and parents to know the surrounding objects and get information about Madrasah Aliyah in Jepara Regency.